Association of new-born birth weight with maternal parameters - Kashyap, Anshika; Kaur, Pushpinder; Srivastava, Puneet; Singh, Veena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Birth weight is the single largest determinant of the neonatal survival and wellbeing. Maternal anaemia is the commonest medical disorder in pregnancy and is associated with significant maternal morbidity and mortality. The effect of haemoglobin levels of the mother on the foetus however remains unclear. This study aims at evaluating the effect of maternal anaemia on neonatal birth weight. It also evaluates the effect of parity, gestational age and maternal age on the new-born birth weight. Methods: A retrospective study was carried out on patients who had delivered in Al Falah hospital, a newly setup medical college in rural Haryana. The population was studied for maternal age, gestational period, and parity and haemoglobin levels. These parameters were correlated with neonatal birth weight. The study was carried out on deliveries which occurred over a period of six months from November 2018 to April 2019. Results: The low birth weight new-borns were 10.5%. Maternal anaemia was present in 79.74 % of women in the study group. Amongst all parameters studied, only higher parity and greater period of gestation had a positive correlation with neonatal birth weight. Haemoglobin levels or maternal age didn’t show a significant impact on the neonatal birth weight. Anaemic mothers didn’t have a higher incidence of low birth weight babies. Conclusion: The most significant contributor to improved neonatal weight is the gestational age of the foetus. All efforts to ensure better neonatal outcome must primarily concentrate on prevention of preterm births. Maternal haemoglobin levels do not directly impact the neonatal birth weight. However, as anaemia is a risk factor for preterm delivery, anaemia indirectly impacts on the neonatal birth weight and outcome.